Factors associated with utilization of antenatal care among rural women in Bangladesh: A community-based cross-sectional study - Md Wahidur Rahman Nizum; Md Mahbubul Alam Shaun; Md Omar Faruk; Md Asaduzzaman Shuvo; Fahmida Fayeza; Md Fakrul Alam; Sujan Kanti Mali; Md Hafizur Rahman; Mohammad Delwer Hossain Hawlader (Clinical Epidemiology and Global Health, 2023)
Background: Despite the Government of Bangladesh's considerable efforts, utilization of antenatal care (ANC) services remains low among Bangladeshi women, notably those from rural areas. Therefore, this study aimed to assess the utilization and underlying factors affecting the utilization of ANC among women of reproductive age in rural Bangladesh. Methods: We conducted a community-based cross-sectional study in three sub-districts of the Rangpur division, Bangladesh, from May 31, 2021, to June 9, 2021. A total of 1195 women with a live birth preceding the survey participated in the study. We used a multivariate logistic regression model to examine the association between all potential factors and the utilization of ANC4/4+ services. Multicollinearity and Hosmer-Lemeshow test was conducted to check the regression model's goodness fit test. Results: The rate of utilization of ANC4/4+ services by women in the three sub-districts of the Rangpur division was 71.7%. Women with more age, education, having more than five members in a family, and being involved in any income-generating activities were more likely to utilize ANC4/4+ in this study. Conclusion: The study found an insufficiency in ANC4/4+ usage, which might lead to missed opportunities for women in rural Bangladesh to have improved maternal outcomes. Particular focus should be given to women's higher education and prioritizing women's autonomy in health seeking issues in the rural women to increase the utilization of ANC4/4+.